CACCI country profile Guyana - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
As a coastal and low-lying country, Guyana is exposed to many climatic hazards, as are the islands in the region. Risks such as flooding, sea level rise, and drought directly impact its development and population. This is due to the increased spread of diseases, contamination of water sources, damage to the agricultural sector, and destruction of forests. Forestry and energy are identified as priority sectors for climate adaptation and mitigation. The agriculture and water sectors can also play an important role in this process. To achieve the goals proposed in its NDC, Guyana has made efforts to create or improve policies and programs. These developments take into consideration the policy needs of the local population and the fact that the main emitting sectors are also vital for the country's economic development and are highly vulnerable to climatic conditions. Approximately 96% of emissions are generated by three specific sectors: land-use change and forestry (as the largest emitter), energy, and finally agriculture.